Semaglutide: Real World Results, Realistic Recommendations - Sanjay Kalra; Nitin Kapoor (Journal of the Pakistan Medical Association, 2026)
In less than a decade, semaglutide has become one of the most frequently used drugs worldwide. This is testimony to not only the burden of obesity that we face, but the benefits of semaglutide as well.1 Along with other glucagon-like peptide 1 receptor agonists (GLP1RA) and dual receptor agonists, semaglutide has proven its weightlowering and pleiotropic effects. Clinical trials and real world studies have demonstrated the efficacy, safety and tolerability of the molecule. Many Asian countries have also been a part of the semaglutide clinical trial programme.2 National level research, however, is needed to supplement the findings of global studies. Each country has a unique nutrimetabolic phenotype, characterized by a specific pattern of adiposity, metabolic dysfunction and nutritional preferences.3 This may impact not only the health status, but also one’s response to therapeutic interventions. Specific dietary choices, gut microbiome, comorbid conditions and concomitant medications, as well as financial constraints and social opinions may influence efficacy and tolerability of these drugs. Continue...